2001
DOI: 10.1097/00005392-200111000-00040
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Iranian Kidney ???Donors???

Abstract: Our sample is a good representative of Iranian kidney vendors, with the majority having psychosocial complications. Globally, the medical community should focus more attention on motivations, quality of life, health and opinions of kidney vendors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(94 citation statements)
references
References 8 publications
5
85
1
3
Order By: Relevance
“…In Pakistan, some sellers report having been pressured or coerced to sell by their landlords or family members,10 11 with kidney selling having become ‘routinized’ as ‘an unpleasant but mundane act’ 10. One study of Iran’s regulated system of paid donation found that several sellers who had borrowed small sums of money from family members were pressured to sell in order to repay this debt, while others reported that their husbands had persuaded or pressured them to sell their kidneys 12. On the face of it, the evidence from existing markets supports the claim that a legal trade in organs would give rise to harmful pressures to sell one’s kidney.…”
Section: Pressure To Vend In Regulated Organ Marketsmentioning
confidence: 99%
“…In Pakistan, some sellers report having been pressured or coerced to sell by their landlords or family members,10 11 with kidney selling having become ‘routinized’ as ‘an unpleasant but mundane act’ 10. One study of Iran’s regulated system of paid donation found that several sellers who had borrowed small sums of money from family members were pressured to sell in order to repay this debt, while others reported that their husbands had persuaded or pressured them to sell their kidneys 12. On the face of it, the evidence from existing markets supports the claim that a legal trade in organs would give rise to harmful pressures to sell one’s kidney.…”
Section: Pressure To Vend In Regulated Organ Marketsmentioning
confidence: 99%
“…268 Some vendors have even reported a diminished quality of life post-transplant. 269 However, as discussed previously, these accounts only depict one side of the story. Without a national transplant registry to publish accurate results, those looking for information about Iran's system are only hearing the loudest voices.…”
Section: ]mentioning
confidence: 99%
“…Another 2001 study of kidney vendors in Iran, where the practice is fully legalised, followed the participants from 6 to 132 months after their operation. 60% of the participants reported negative effects on their physical abilities, most such participants being unskilled labourers 6. Vending caused negative effects on employment in 65%, in some part stemming from postoperative depression, anxiety over losing the kidney, and fear of doing damage to themselves through certain forms of employment.…”
Section: The Limits Of Double Bind Reasoningmentioning
confidence: 99%